1992
DOI: 10.1016/0042-6822(92)90694-k
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of adenovirus 12 DNA-binding protein but not DNA polymerase during abortive infection of hamster cells

Abstract: Replication of human adenovirus type 12 DNA is blocked in abortively infected baby hamster kidney cells. The activity and accumulation of adenovirus 12 DNA polymerase is equivalent in infected hamster and human cell extracts. However, the accumulation of adenovirus type 12 DNA-binding protein is approximately 120-fold lower in extracts from infected hamster cells when compared to infected permissive human cells. This difference in accumulation is not due to replication of viral DNA during productive infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…That these sites exist is suggested by indirect immunofluorescence experiments that showed that Ad replication proteins are present at punctate sites within the nucleus (11,24,42), perhaps within large complexes of NM proteins. Localized concentrations of viral factors may be critical for the occurrence of successful Ad DNA replication (32). For example, it has been shown that the Ad replication protein, DNA-binding protein, is part of a 650-kDa, high-salt, stable complex which contains both DNA binding and kinase activities (45).…”
Section: Discussionmentioning
confidence: 99%
“…That these sites exist is suggested by indirect immunofluorescence experiments that showed that Ad replication proteins are present at punctate sites within the nucleus (11,24,42), perhaps within large complexes of NM proteins. Localized concentrations of viral factors may be critical for the occurrence of successful Ad DNA replication (32). For example, it has been shown that the Ad replication protein, DNA-binding protein, is part of a 650-kDa, high-salt, stable complex which contains both DNA binding and kinase activities (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of the DBP gene lagged behind that observed in ovine and nonovine fibroblasts. Diminished expression of E2 genes was suggested as a major cause of the early block in Ad12 replication in hamster cells, although reports about the levels of single E2 gene products are contradictory (21,36). Reduced amounts of E1 mRNAs were also reported for abortive Ad12 infection (35).…”
Section: Discussionmentioning
confidence: 99%
“…This abortive infection was bypassed by overexpressing the adenovirus serotype 5 E1 region in cell culture. In this case, E1 region overexpression was sufficient to circumvent transcriptional blocks in this model (22). These studies indicate that expression of viral genes or coinfection with other viruses may provide the unknown factors required to allow the progression of an abortive infection.…”
Section: Discussionmentioning
confidence: 71%